Wind-resistant optimal design of tall buildings based on improved genetic algorithm. (October 2020) - Li, Yi; Duan, Ru-Biao; Li, Qiu-Sheng; Li, Yong-Gui; Huang, Xuan
Abstract: Modern tall buildings are likely sensitive to wind excitations due to their increasing height and structural flexibility. Proper or optimal wind-resistant structural design of such high-rise buildings is required or sometimes necessary to meet the requirement of safety and serviceability. Combining a genetic algorithm (GA) with improved penalty function and calculation method for equivalent static wind loads (ESWLs), this paper presents an optimal procedure for the wind-resistant design of tall buildings, which aims to minimize the total weight of the designed building subject to the constraints of top acceleration and lateral drifts. A penalty function is utilized to deal with the implicit expressed constraints of optimization. The ESWLs can be instantaneously updated due to the change of structural dynamic properties during the optimal design process. A 60-story rectangular reinforced concrete frame structure with the same geometric shape of the CAARC standard tall building is adopted to verify the feasibility of the presented method. The example demonstrates that the proposed optimal design procedure is an effective tool for the wind-resistant optimal design of tall buildings.